Retrograde trans-synaptic visual pathway degeneration in multiple sclerosis: A case series - Al-Louzi, Omar (Mult Scler, 2017)
BACKGROUND: Trans-synaptic degeneration (TSD) describes the propagation of neuronal injury through synaptic pathways in the human nervous system and may be linked to the accelerated retinal atrophy seen in multiple sclerosis (MS). RESULTS: We report six cases where homonymous, hemi-macular ganglion cell + inner plexiform (GCIP) thickness reduction was seen in conjunction with posterior visual pathway lesions. Macular microcystoid changes of the inner nuclear layer (INL) were seen in a subset of three subjects. CONCLUSION: Our findings highlight the utility of assessing regional GCIP changes to identify potential retrograde TSD in MS and demonstrate that INL changes may be an accompaniment in such instances.